El nuevo reglamento de las tarjetas electrónicas - Romero-Pérez, Jorge Enrique (2014)
New regulations of the electronic cards have been issued. These rules should reconcile the interests of the parties of this modern commercial contract. Certainly, cardholders are the weak element in this contractual relationship, and they must be protected. Usury interests, over 30%, should be lawfully limited. In the market there are cards charging more than 30%. These interests are so high that they must eliminated from the body of laws. Marketing tactics are varied: cash rebate, cash back based on a point system as per the card the level of use; acquisition of goods and services for certain amounts with card use, catalogs of goods and services based on the same system, delivery of cash amounts, discounts in restaurants and other stores when paying with credit cards, etc. A law is still needed to regulate these cards adequately. The regulations are not enough, but they are convenient to the interests of card issuers. Within the range of points of view to analyze these cards, I place myself as a cardholder since these payment instruments appeared in the country.